Enhanced Nonlinear Yield from Barium Titanate Metasurface Down to the Near Ultraviolet. Issue 22 (2nd September 2019) - Timpu, Flavia; Reig Escalé, Marc; Timofeeva, Maria; Strkalj, Nives; Trassin, Morgan; Fiebig, Manfred; Grange, Rachel
Abstract: Metasurfaces are artificial nanopatterned 2D architectures that can offer a solution to the bottleneck problem of bulky optical elements. They have the ability of wavefront shaping and light sub‐wavelength manipulation because they are formed of resonantly scattering elements. Recently, the properties of metasurfaces gained interest for nonlinear optics in the efforts to miniaturize nonlinear optical devices while maintaining high photon–photon interactions. Herein, a new type of nonlinear metasurface based on the metal oxide barium titanate is developed, which demonstrates an efficient nonlinear optical response over a broad spectral range, from near‐ultraviolet to the visible range, where metals and semiconductors typically have losses. Contrary to previously demonstrated nonlinear plasmonic metasurfaces, these dielectric metasurfaces are less sensitive to surface roughness and gain their optical nonlinearity from the noncentrosymmetric crystal structure of the ferroelectric barium titanate. Abstract : A new type of nonlinear metasurface suitable in a broad range down to the near‐UV is developed and tested. The metasurface is fabricated from barium titanate, an intrinsically nonlinear dielectric and ferroelectric material, by using a novel top‐down fabrication method employed on thin films grown by pulsed laser deposition.